Coming Of Age: An Analysis of A Young Adult Character Development In Ellen Hopkins’ Crank - Rizky Fajarani (Passage, 2013)
The present research entitled Coming of Age: An Analysis of a Young Adult Character Development in Ellen Hopkins’ “Crank” is a textual analysis of Ellen Hopkins’ young adult fiction focusing on the issue of coming of age in the novel. The discussion focuses on the main female character in the story to reveal the ways coming of age issue is addressed in the novel. Therefore, the discussion is framed within the theories of the characteristic and development of young adult (Bucher and Hinton, 2010), coming of age (e.g. Millard, 2007 and Fox, 2010) and identity (Barker, 2002). The research utilizes a qualitative method particularly textual analysis. The result of the present research shows that coming of age describes a progress shift which is experienced by the main character, Georgia, from a teenage girl who is simple-minded to a mature adult with higher-level of thinking. In other words, coming of age issue shows the process of adolescents from immaturity to maturity. Keywords: Coming of Age, Young Adult, Character Development, Identity